Neuroprotective effects of sesamol against LPS-induced spatial learning and memory deficits are mediated via anti-inflammatory and antioxidant activities in the rat brain - Zahra Beheshtimanesh; Ziba Rajaei (Mashhad University of Medical Sciences, 2023)
Objective: Sesamol is a phenolic lignan extracted from sesame seeds, and it possesses anti-inflammatory and antioxidant activities. Lipopolysaccharide (LPS) is known to produce neuroinflammatory responses and memory impairment. The current study aimed to investigate the protective influence of sesamol against LPS-mediated neuroinflammation and memory impairment.Materials and Methods: Sesamol (10 and 50 mg/kg) was injected to Wistar rats for two weeks. Then, animals received LPS injection (1 mg/kg) for five days, while treatment with sesamol was performed 30 min before LPS injection. Spatial learning and memory were assessed by the Morris water maze (MWM), two hours after LPS injection on days 15-19. Biochemical assessments were performed after the end of behavioral experiments.Results: LPS-administered rats showed spatial learning and memory deficits, since they spent more time in the MWM to find the hidden platform and less time in the target quadrant. Besides these behavioral changes, tumor necrosis factor-α (TNF-α) and lipid peroxidation levels were increased, while total thiol level was decreased in the hippocampus and/or cerebral cortex. In addition, sesamol treatment (50 mg/kg) for three weeks decreased the escape latency and increased the time on probe trial. Sesamol also reduced lipid peroxidation and TNF-α level, while enhanced total thiol level in the brain of LPS-exposed rats.Conclusion: Supplementation of sesamol attenuated learning and memory impairments in LPS-treated rats via antioxidative and anti-inflammatory activities in the rat brain.